Degree Distribution of Arbitrary AANET. (28th February 2015) - Liu, Xue; Zeng, Xiaoping; Wang, Zhiming; Chen, Li; Jin, Yuemei
Abstract : Taking the safe distance between two adjacent planes in the same airline into account, we give a model for the multiairline aeronautical ad hoc network (AANET). Based on our model, we analyze the plane's degree distribution of any arbitrary AANET. Then, the expressions of the degree distributions of one single plane and the whole networks are both worked out and verified by the simulations, in which we generate several random AANETs. Since our model is a reasonable abstraction of the real situation, the theoretical result we get is very close to the result of the real networks, which is also shown in the simulations.